Sarcolemmal and mitochondrial K(ATP) channels and myocardial ischemic preconditioning - Peart, J. N. (J Cell Mol Med, 2007)
Ischemic preconditioning (IPC) is the phenomenon whereby brief periods of ischemia have been shown to protect the myocardium against a sustained ischemic insult. The result of IPC may be manifest as a marked reduction in infarct size, myocardial stunning, or incidence of arrhythmias. While many substances and pathways have been proposed to play a role in the signal transduction mediating the cardioprotective effect of IPC, overwhelming evidence indicates an intimate involvement of the ATP‐sensitive potassium channel (K(ATP) channel) in this process. Initial hypotheses suggested that the surface or sarcolemmal K(ATP) (sarcK(ATP)) channel mediated the cardioprotective effects of IPC. However, much research has subsequently supported a major role for the mitochondrial K(ATP) channel (mitoK(ATP)) as the one involved in IPC‐mediated cardioprotection. This review presents evidence to support a role for the sarcK(ATP) or the mitoK(ATP) channel as either triggers and/or downstream mediators in the phenomenon of IPC.